Pengaruh Ukuran Perusahaan, Komite Audit, Audit Tenure dan Leverage terhadap Kualitas Audit pada Sektor Kesehatan - Chelsea, Chelsea; Olivia, Theresia (Lembaga Teewan Journal Solutions, 2026)
This study aims to examine the effect of firm size, audit committee, audit tenure, and leverage on audit quality in healthcare sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Audit quality is important because reliable financial statements support stakeholders in making economic decisions. This study used a quantitative approach with secondary data obtained from audited financial statements and annual reports. The population consisted of 35 healthcare sector companies listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling, resulting in 27 companies that met the criteria. With four years of observation, the study used 108 company-year observations. The data were analyzed using logistic regression with IBM SPSS version 26. The results show that audit tenure has a positive and significant effect on audit quality. Meanwhile, firm size, audit committee, and leverage do not significantly affect audit quality. This finding indicates that a longer auditor-client relationship can improve audit quality through better auditor understanding of the client’s business and audit risks.